Semi-solid-state battery electrolyte precursor, semi-solid-state battery electrolyte, semi-solid-state battery and preparation method thereof
By using copolymers of acrylic monomers and fluorine-containing unsaturated monomers in semi-solid batteries, the electrode/electrolyte interface is optimized, and the problems of unstable interface performance and high battery impedance are solved, thereby reducing DC internal resistance and improving battery Performance effect.
Patent Information
- Application Number
- CN202411281744.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
AI Technical Summary
Existing semi-solid state batteries have problems of unstable interface performance and high battery impedance, especially the monomer residues and interface side reactions caused by high temperature curing stages increase the DC internal resistance (DCIR) of the battery cell, affecting the safety of the battery. and energy density.
Using semi-solid battery electrolyte precursors including acrylic monomers and fluorine-containing unsaturated monomers, copolymers are formed through in-situ polymerization technology, the electrode/electrolyte interface is optimized, and the SEI film formation that is involved in the residual monomer is reduced, and the DC resistance is reduced. And simplify the preparation process.
It significantly reduces the DC internal resistance of the battery, improves the stability of the electrode/electrolyte interface and the cycling performance of the battery, simplifies the preparation process, and enhances the feasibility of large-scale applications of the battery.
Smart Images

Figure BDA0005043178920000091 
Figure BDA0005043178920000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a semi-solid battery electrolyte precursor, a semi-solid battery electrolyte, a semi-solid battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in electronic products and electric vehicles. Although great achievements have been made in the field of high energy density battery systems, problems such as electrolyte leakage and battery short circuits are still major safety hazards, which seriously hinder the further development of lithium-ion batteries. When there is an internal or external short circuit, undesirable exothermic reactions may lead to a rapid increase in internal temperature and thermal runaway.
[0003] Solid-state batteries are proposed to improve and replace traditional liquid electrolytes and fundamentally solve safety issues. In all-solid-state batteries, thermally stable solid polymer electrolytes or inorganic solid electrolytes are used instead of liquid electrolytes, which helps to avoid electrolyte leakage and combustion and explosion.
[0004] However, all-solid-state batteries still have some problems, such as poor contact between electrolyte and electrode, and lack of scalable preparation technology. In order to solve these challenges of all-solid-state batteries, constructing semi-solid batteries through in-situ polymerization technology is considered to be one of the most promising solutions to improve the safety performance of lithium-ion batteries. Gel electrolyte combines the advantages of liquid electrolyte and solid polymer electrolyte, and has good ionic conductivity and interface compatibility. Inside the lithium-ion battery, the gel electrolyte can regulate the uniform distribution of lithium ion flow, inhibit the decomposition reaction of the electrolyte, and improve the electrode stability and battery safety. Semi-solid batteries made of gel electrolytes have both high safety and high energy density, and have great development potential compared to traditional liquid batteries.
[0005] In-situ polymerization is a method for preparing semi-solid batteries. Since it is compatible with the existing battery preparation process, it can achieve mass production without changing a large number of processes, so it has broad development prospects. Semi-solid batteries prepared by in-situ polymerization have problems such as difficulty in controlling the degree of monomer polymerization and more side reactions on the interface caused by residual initiators, which makes the DCIR of the battery higher than that of the liquid system and difficult to apply in practice. The existing process usually adopts the method of preparing the precursor solution, injecting the liquid, forming it, and then curing it at high temperature, which causes the polymerized monomer to participate in the film formation of SEI in the formation stage, forming an interface with large impedance. The process route is optimized for this. After the liquid is injected, high-temperature curing is first performed, and then formation is performed. However, the problem of high initial DCIR of the battery still exists. This is mainly because the film-forming additives containing unsaturated bonds are consumed in the high-temperature curing stage, and the monomer polymerization is incomplete, resulting in residues. The residual monomers may participate in the film formation of SEI in the subsequent formation stage, thereby increasing the DCIR of the battery. At present, there have been reports on process improvements, which improve the DCIR of gel semi-solid batteries through secondary injection. The first injection is to inject liquid electrolyte, and then the second injection is performed after formation. The precursor solution of the secondary injection is a mixed solution of electrolyte, monomer and initiator. Although this method can reduce the DCIR of the battery cell to a certain extent, it increases the complexity of the process and the time cost. Summary of the invention
[0006] The main purpose of the present invention is to provide a semi-solid battery electrolyte precursor, a semi-solid battery electrolyte, a semi-solid battery and a preparation method thereof, so as to solve the problems of unstable interface performance and high battery impedance of the semi-solid battery in the prior art.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a semi-solid battery electrolyte precursor is provided, which comprises: a first polymer monomer, a second polymer monomer and an initiator; wherein the first polymer monomer is an acrylic monomer or an acrylate monomer; and the second polymer monomer is a fluorine-containing unsaturated monomer.
[0008] Further, the first polymer monomer includes any one or more of acrylic acid, methacrylic acid, methyl methacrylate, butyl acrylate, 1,3-butanediol diacrylate, pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and pentaerythritol triacrylate; preferably, the first polymer monomer includes any one or more of methyl methacrylate, butyl acrylate, 1,3-butanediol diacrylate, pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and pentaerythritol triacrylate;
[0009] The second polymer monomer includes any one or more of 2,2,2-trifluoroethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate and 1,1,1,3,3,3-hexafluoroisopropyl methacrylate;
[0010] The initiator includes any one or more of azobisisobutyronitrile, azobisisoheptylnitrile, benzoyl, dicumyl peroxide, dibenzoyl peroxide, potassium persulfate and ammonium persulfide.
[0011] Further, the mass ratio of the first polymer monomer to the second polymer monomer is 3:1-1:1, preferably 3:1-2:1;
[0012] Preferably, the mass of the initiator is 0.5-2 wt % of the total mass of the first polymer monomer and the second polymer monomer.
[0013] Furthermore, the semi-solid battery electrolyte precursor also includes a lithium salt and a solvent;
[0014] The lithium salt includes any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate, lithium perchlorate, and lithium dioxalatoborate;
[0015] The solvent includes any one or more of propylene carbonate, ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dimethyl ether and ethyl propionate.
[0016] Furthermore, the mass of the first polymer monomer is 0.5-5wt% of the total mass of the semi-solid battery electrolyte precursor, and the mass of the second polymer monomer is 0.5-2.5wt% of the total mass of the semi-solid battery electrolyte precursor;
[0017] Preferably, the sum of the mass of the first polymer monomer and the second polymer monomer accounts for 1.5%-3% of the total mass of the semi-solid battery electrolyte precursor.
[0018] In order to achieve the above object, according to one aspect of the present invention, a semi-solid battery electrolyte is provided. The semi-solid electrolyte is obtained by in-situ polymerization of any of the above-mentioned semi-solid battery electrolyte precursors.
[0019] According to another aspect of the present invention, a method for preparing a semi-solid-state battery is provided, the method comprising: injecting any of the above-mentioned semi-solid-state battery electrolyte precursors into a battery cell for in-situ polymerization.
[0020] Further, the temperature of the in-situ polymerization is 50-70° C., and the time of the in-situ polymerization is 6-12 h;
[0021] Preferably, before the in-situ polymerization, the semi-solid battery electrolyte precursor is injected into the battery cell, vacuum packaged, and left to stand for 24-50 hours.
[0022] Further, it includes: preparing the positive electrode sheet, the negative electrode sheet and the separator into a dry battery cell;
[0023] Preferably, the positive electrode material of the positive electrode sheet includes any one or more of lithium cobalt oxide, ternary material, lithium iron phosphate, lithium-rich manganese-based material and spinel lithium manganese oxide;
[0024] Preferably, the negative electrode material of the negative electrode sheet includes any one or more of graphite, amorphous carbon, lithium titanate, SiOx / C composite material and Sn-based composite material.
[0025] According to another aspect of the present invention, there is provided a semi-solid-state battery, which is prepared by any of the above-mentioned methods for preparing a semi-solid-state battery or includes the above-mentioned semi-solid-state battery electrolyte.
[0026] By applying the technical solution of the present invention, the semi-solid battery electrolyte precursor of the present application selects the above-mentioned first polymer monomer with acrylic acid or acrylate structure and the second polymer monomer with fluorine-containing unsaturated structure, and the formed copolymer can improve the stability of the electrode / electrolyte interface. Even if there are monomer residues, an SEI film with good stability can be formed in the subsequent film formation stage to optimize the electrode / electrolyte interface. At the same time, the semi-solid battery electrolyte precursor of the present application is suitable for a large number of monomer types, and different electrolyte systems can be designed according to battery requirements. The subsequent preparation process for semi-solid batteries is simple, and while significantly reducing the direct current internal resistance (DCIR), it can improve the preparation efficiency of the battery and has good feasibility for large-scale application. DETAILED DESCRIPTION
[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0028] As analyzed in the background technology of this application, there are problems in the prior art of unstable interface performance and high battery impedance of semi-solid batteries. In order to solve this problem, this application provides a semi-solid battery electrolyte precursor, a semi-solid battery electrolyte, a semi-solid battery and a preparation method thereof.
[0029] According to a typical embodiment of the present application, a semi-solid battery electrolyte precursor is provided, which includes: a first polymer monomer, a second polymer monomer and an initiator; the first polymer monomer is an acrylic monomer or an acrylate monomer; and the second polymer monomer is a fluorine-containing unsaturated monomer.
[0030] The semi-solid battery electrolyte precursor of the present application selects the above-mentioned first polymer monomer with acrylic acid or acrylate structure and the second polymer monomer with fluorine-containing unsaturated structure. The copolymer formed can improve the stability of the electrode / electrolyte interface. Even if there are monomer residues, an SEI film with good stability can be formed in the subsequent film formation stage to optimize the electrode / electrolyte interface. At the same time, the semi-solid battery electrolyte precursor of the present application is suitable for a large number of monomer types, and different electrolyte systems can be designed according to battery requirements. The subsequent preparation process for semi-solid batteries is simple, and while significantly reducing the direct current internal resistance (DCIR), it can improve the preparation efficiency of the battery and has good feasibility for large-scale application.
[0031] The acrylic monomers mentioned above refer to acrylic acid or compounds in which vinyl hydrogen in acrylic acid is substituted by hydrocarbon groups, such as acrylic acid, methacrylic acid, 2-ethylacrylic acid, 2-propylacrylic acid, crotonic acid, 3,3-dimethylacrylic acid, etc., but are not limited thereto.
[0032] The above-mentioned acrylic acid ester monomer refers to the ester monomer corresponding to the above-mentioned acrylic acid monomer, which may be its methyl ester, ethyl ester, propyl ester, butyl ester, 1,3-butanediol ester, pentaerythritol ester, etc., but is not limited thereto. In particular, when the above-mentioned first polymer monomer contains an acrylic acid ester monomer, the copolymer formed by it and the fluorine-containing unsaturated monomer can further improve the stability of the electrode / electrolyte interface, reduce the DC resistance, and thus improve the performance of the semi-solid titanium battery.
[0033] In some preferred embodiments of the present application, the above-mentioned first polymer monomer includes any one or more of acrylic acid, methacrylic acid, methyl methacrylate, butyl acrylate, 1,3-butanediol diacrylate, pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and pentaerythritol triacrylate, which not only have a wide range of sources, but also can play a better role in the semi-solid battery electrolyte precursor of the present application to reduce the DCIR of the battery.
[0034] In some typical embodiments of the present application, the first polymer monomer includes any one or more of methyl methacrylate, butyl acrylate, 1,3-butanediol diacrylate, pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and pentaerythritol triacrylate, which can further reduce the internal resistance of the battery and improve the cycle performance.
[0035] In some preferred embodiments of the present application, the second polymer monomer includes any one or more of 2,2,2-trifluoroethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate and 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, which is convenient for polymerization with the first polymer monomer, and the formed copolymer has a more significant effect on improving interface stability and reducing DC resistance, thereby further improving the performance of the battery.
[0036] The initiator is any compound that can initiate the polymerization reaction of the first polymer monomer and the second polymer monomer, and can be selected from the prior art, and the present application has no special requirements for this. For example, the initiator includes but is not limited to any one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl, dicumyl peroxide, dibenzoyl peroxide, potassium persulfate and ammonium persulfide.
[0037] In order to better play the role of the first polymer monomer and the second polymer monomer in the semi-solid battery electrolyte precursor, in some embodiments of the present application, the mass ratio of the first polymer monomer to the second polymer monomer is 3:1-1:1, preferably 3:1-2:1.
[0038] In some embodiments of the present application, the mass of the initiator is 0.5-2wt% of the total mass of the first polymer monomer and the second polymer monomer. When the electrolyte precursor is applied to battery preparation, the polymer monomer has a more suitable polymerization rate, which is beneficial to further improve the performance of the battery.
[0039] The semi-solid electrolyte precursor of the present application may further include conventional electrolyte components, such as lithium salt and solvent, in addition to the above-mentioned first polymer monomer, second polymer monomer and initiator.
[0040] The specific type of lithium salt or solvent can be selected in the prior art, and the present application has no particular restrictions. In some embodiments of the present application, the lithium salt includes any one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium bisfluorosulfonyl imide (LiFSI), lithium difluorooxalate borate (LiODFB), lithium perchlorate (LiClO4) and lithium dioxalate borate (LiBOB). In some embodiments of the present application, the above-mentioned solvent includes any one or more of propylene carbonate (PC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dimethyl ether (DME) and ethyl propionate (EP).
[0041] In some embodiments of the present application, in order to further improve the performance of the battery and enhance the role of the copolymer formed by polymerization in stabilizing the interface, the mass of the first polymer monomer is 0.5-5wt% of the total mass of the semi-solid battery electrolyte precursor, and the mass of the second polymer monomer is 0.5-2.5wt% of the total mass of the semi-solid battery electrolyte precursor. Exemplarily, the mass of the first polymer monomer is 0.5wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt%, 4.7wt% or 5wt% of the total mass of the semi-solid battery electrolyte precursor. Illustratively, the mass of the second polymer monomer is 0.5wt%, 0.7wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.2wt% or 2.5wt% of the total mass of the semi-solid battery electrolyte precursor.
[0042] In some preferred embodiments of the present application, the sum of the mass of the first polymer monomer and the second polymer monomer accounts for 1.5%-3% of the total mass of the semi-solid battery electrolyte precursor. As an example, the sum of the mass of the first polymer monomer and the second polymer monomer accounts for 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3% of the total mass of the semi-solid battery electrolyte precursor.
[0043] In some typical embodiments of the present application, the mass of the first polymer monomer is 0.5-5wt% of the total mass of the semi-solid battery electrolyte precursor, the mass of the second polymer monomer is 0.5-2.5wt% of the total mass of the semi-solid battery electrolyte precursor, and the mass ratio of the first polymer monomer to the second polymer monomer is 3:1-1:1, preferably 3:1-2:1, and the mass of the initiator is 0.5-2wt% of the total mass of the first polymer monomer and the second polymer monomer. The electrolyte containing the fluorine-containing copolymer formed by the semi-solid battery electrolyte precursor has better comprehensive performance, and the semi-solid battery containing it has a relatively stable electrode / electrolyte interface and a lower DCIR.
[0044] The above-mentioned semi-solid battery electrolyte precursor may also contain additives. The types and amounts of the additives may refer to the prior art. Those skilled in the art may add the types and amounts of the additives in the electrolyte in the prior art to the electrolyte precursor of the present application. Herein, the present application will not introduce them in detail.
[0045] According to another typical embodiment of the present application, a semi-solid battery electrolyte is provided. The semi-solid battery electrolyte is obtained by in-situ polymerization of any of the above-mentioned semi-solid battery electrolyte precursors.
[0046] Since the above-mentioned semi-solid battery electrolyte precursor selects the above-mentioned first polymer monomer with acrylic acid or acrylate structure and the second polymer monomer with fluorine-containing unsaturated structure, the copolymer formed in the semi-solid battery electrolyte by in-situ polymerization can improve the stability of the electrode / electrolyte interface. Even if there are monomer residues, a SEI film with good stability can be formed in the subsequent film formation stage to optimize the electrode / electrolyte interface. At the same time, since the semi-solid battery electrolyte precursor of the present application is compatible with a large number of monomer types, different electrolyte systems can be designed according to battery requirements, and the subsequent preparation process for semi-solid batteries is simple. While significantly reducing the direct current internal resistance (DCIR), it can improve the preparation efficiency of the battery and has good feasibility for large-scale application.
[0047] According to another typical embodiment of the present application, a method for preparing a semi-solid-state battery is provided, the method comprising: injecting any of the above-mentioned semi-solid-state battery electrolyte precursors into a battery cell for in-situ polymerization.
[0048] The preparation method allows the first polymer monomer with an acrylic acid or acrylate structure and the second polymer monomer with a fluorine-containing unsaturated structure to be polymerized in situ under the action of an initiator. The formed copolymer can improve the stability of the electrode / electrolyte interface. Even if there are monomer residues, an SEI film with good stability can be formed in the subsequent film formation stage, optimizing the electrode / electrolyte interface, significantly reducing the DC resistance of the battery, and improving the battery's cycle performance. In addition, compared with methods such as secondary injection, this method does not add other process flows, reduces time costs, improves efficiency, and has good feasibility for large-scale application.
[0049] In some embodiments of the present application, after the above-mentioned semi-solid battery electrolyte precursor is injected into the battery cell, the temperature for in-situ polymerization is 50-70°C, the time for in-situ polymerization is 6-12h, and the formed electrolyte containing fluorine-containing copolymer has relatively excellent performance.
[0050] In some preferred embodiments of the present application, before in-situ polymerization, a semi-solid battery electrolyte precursor is injected into the battery cell, vacuum-sealed, and left to stand for 24-50 hours to ensure that the electrolyte fully infiltrates the electrode. Preferably, the process is carried out at 15-35°C or room temperature.
[0051] In some embodiments of the present application, the preparation method includes: preparing a positive electrode sheet, a negative electrode sheet and a separator into a dry battery cell. In the preparation method of the semi-solid battery of the present application, there is no limitation on the type and preparation method of the positive electrode sheet, the negative electrode sheet and the separator, and those skilled in the art can select from the existing technology.
[0052] In some typical embodiments of the present application, the positive electrode material of the positive electrode sheet includes any one or more of lithium cobalt oxide, ternary material, lithium iron phosphate, lithium-rich manganese-based material and spinel lithium manganese oxide.
[0053] In some typical embodiments of the present application, the negative electrode material of the negative electrode sheet includes any one or more of graphite, amorphous carbon, lithium titanate, SiOx / C composite material and Sn-based composite material.
[0054] In some typical embodiments of the present application, the preparation method of the above-mentioned semi-solid battery includes: step 1, electrolyte precursor preparation: mixing lithium salt, solvent, additive, first polymer monomer, second polymer monomer and initiator; step 2, battery cell preparation: assembling the positive electrode sheet, negative electrode sheet and separator into the shell to prepare a dry battery cell; step 3, liquid injection packaging: injecting the configured electrolyte into the dry battery cell, vacuum packaging, and standing at room temperature for 24-50h; step 4, in-situ polymerization: the battery cell is standing in an oven at 50-70℃ for 6-12h; step 5, chemical formation: forming at 40-50℃, and dividing at room temperature to prepare a semi-solid battery. Preferably, the formation temperature is 45℃.
[0055] According to another typical embodiment of the present application, a semi-solid-state battery is provided. The semi-solid-state battery is prepared by any of the above-mentioned methods for preparing a semi-solid-state battery or includes the above-mentioned semi-solid-state battery electrolyte.
[0056] The semi-solid battery prepared by the above preparation method is characterized in that a first polymer monomer having an acrylic acid or acrylate structure and a second polymer monomer having a fluorine-containing unsaturated structure are in situ polymerized under the action of an initiator, and the formed semi-solid electrolyte containing the above copolymer can improve the stability of the electrode / electrolyte interface. Even if there are monomer residues, an SEI film with good stability can be formed in the subsequent film formation stage, the electrode / electrolyte interface is optimized, the DC resistance of the battery can be significantly reduced, and the cycle performance of the battery is significantly improved.
[0057] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.
[0058] Example 1
[0059] Preparation of electrolyte precursor:
[0060] Adding 7.5 g of pentaerythritol tetraacrylate, 2.5 g of 2,2,2-trifluoroethyl methacrylate and 0.1 g of azobisisobutyronitrile to 490 g of the electrolyte to prepare an electrolyte precursor;
[0061] The electrolyte consists of a lithium salt, an organic solvent and an additive. The lithium salt is 1M LiPF6, the organic solvent is a mixture of vinyl carbonate EC and ethyl methyl carbonate EMC in a volume ratio of 3:7, and the additive is 3wt% vinylene carbonate VC and 1wt% fluoroethylene carbonate FEC.
[0062] Preparation of square dry cells:
[0063] The positive electrode slurry is obtained by mixing 96wt% of the positive electrode active material nickel-cobalt-manganese ternary material, 2.8wt% of the conductive agent, and 1.2wt% of the binder with the solvent. The positive electrode slurry is then evenly coated on both sides of the positive electrode current collector, and the positive electrode sheet is obtained through drying, rolling, slitting, and other steps;
[0064] The negative electrode slurry is obtained by mixing and stirring 96wt% of negative electrode active material graphite, 2wt% of conductive agent, and 2wt% of binder with solvent. Then the negative electrode slurry is evenly coated on both sides of the negative electrode current collector, and the negative electrode sheet is obtained through drying, rolling and other steps;
[0065] The positive electrode sheet, the negative electrode sheet and the separator are assembled into a shell to obtain a square dry battery cell.
[0066] Liquid injection packaging: Inject the prepared electrolyte precursor into the square dry battery cell, vacuum package it, and let it stand at room temperature for 48 hours.
[0067] In-situ polymerization: The battery cell was placed in an oven at 60°C for 6 hours.
[0068] Chemical formation and capacity separation: The chemical formation is carried out at 45°C and the capacity separation is carried out at room temperature to prepare a square semi-solid-state battery.
[0069] Example 2
[0070] The difference from Example 1 is that in the preparation of the electrolyte precursor, the same mass of methyl methacrylate is used to replace pentaerythritol tetraacrylate.
[0071] Example 3
[0072] The difference from Example 1 is that in the preparation of the electrolyte precursor, the same mass of methacrylic acid is used to replace pentaerythritol tetraacrylate.
[0073] Example 4
[0074] The difference from Example 1 is that in the preparation of the electrolyte precursor, the same mass of 2,2,3,3,3-pentafluoropropyl methacrylate is used to replace 2,2,2-trifluoroethyl methacrylate.
[0075] Example 5
[0076] The difference from Example 1 is that in the preparation of the electrolyte precursor, the added amount of 2,2,2-trifluoroethyl methacrylate is 7.5 g.
[0077] Example 6
[0078] The difference from Example 1 is that in the preparation of the electrolyte precursor, the added amount of 2,2,2-trifluoroethyl methacrylate is 10 g.
[0079] Example 7
[0080] The difference from Example 1 is that in the preparation of the electrolyte precursor, the added amount of 2,2,2-trifluoroethyl methacrylate is 1.5 g.
[0081] Example 8
[0082] The difference from Example 1 is that in the preparation of the electrolyte precursor, the amount of pentaerythritol tetraacrylate added is 2.5 g.
[0083] Example 9
[0084] The difference from Example 1 is that in the preparation of the electrolyte precursor, the amount of pentaerythritol tetraacrylate added is 25 g, the amount of 2,2,2-trifluoroethyl methacrylate added is 10 g, and the amount of initiator added is 0.7 g.
[0085] Example 10
[0086] The difference from Example 1 is that during the in-situ polymerization, the battery cell is left to stand at 70° C. in an oven for 5 hours.
[0087] Comparative Example 1
[0088] The difference from Example 1 is that in the preparation of the electrolyte precursor, 10 g of pentaerythritol tetraacrylate is added to the electrolyte, but no 2,2,2-trifluoroethyl methacrylate is added.
[0089] Comparative Example 2
[0090] The difference from Example 1 is that in the preparation of the electrolyte precursor, 10 g of 2,2,2-trifluoroethyl methacrylate is added to the electrolyte, but pentaerythritol tetraacrylate is not added.
[0091] Comparative Example 3
[0092] The difference from Example 1 is that in the preparation of the electrolyte precursor, the same mass of fluoroethylene carbonate is used to replace pentaerythritol tetraacrylate.
[0093] Comparative Example 4
[0094] The difference from Example 1 is that in the preparation of the electrolyte precursor, the same mass of vinyl ethylene carbonate is used to replace pentaerythritol tetraacrylate.
[0095] Comparative Example 5
[0096] The difference from Example 1 is that in the preparation of the electrolyte precursor, the same mass of N,N-dimethylacrylamide is used to replace pentaerythritol tetraacrylate.
[0097] The square semi-solid batteries prepared in the above examples and comparative examples were tested according to the following method, and the test results are listed in Table 1.
[0098] DCIR: At 50% SOC, the test battery is charged and discharged at a constant current I of 1C, the charge and discharge time is 10s, and the time recording condition is 1s. Record the voltage change ΔU during the charge or discharge process, DCIR = ΔU / I.
[0099] Electrochemical performance: At room temperature, the battery was charged at 1C constant current and constant voltage to 4.2V, cut off at 0.05C, and allowed to stand for 10 minutes. The battery was discharged at 1C constant current to 2.75V and allowed to stand for 10 minutes. After 600 cycles, the capacity retention rate was obtained.
[0100] Table 1
[0101]
[0102]
[0103] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the above-mentioned semi-solid battery electrolyte precursor selects the above-mentioned first polymer monomer with acrylic acid or acrylate structure and the second polymer monomer with fluorine-containing unsaturated structure, and the formed copolymer can improve the stability of the electrode / electrolyte interface. Even if there are monomer residues, a SEI film with good stability can be formed in the subsequent film formation stage to optimize the electrode / electrolyte interface. At the same time, the semi-solid battery electrolyte precursor of the present application is suitable for a large number of monomer types, and different electrolyte systems can be designed according to battery requirements. The subsequent preparation process for semi-solid batteries is simple, and while significantly reducing the direct current internal resistance (DCIR), it can improve the preparation efficiency of the battery and has good feasibility for large-scale application.
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A semi-solid battery electrolyte precursor, It is characterized in that include: A first polymer monomer, a second polymer monomer, and an initiator; The first polymer monomer is an acrylic monomer or an acrylic ester monomer; The second polymer monomer is a fluorine-containing unsaturated monomer.
2. The semi-solid battery electrolyte precursor according to claim 1, It is characterized in that The first polymer monomer includes any one or more of acrylic acid, methacrylic acid, methyl methacrylate, butyl acrylate, 1,3-butanediol diacrylate, pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and pentaerythritol triacrylate; preferably, the first polymer monomer includes any one or more of methyl methacrylate, butyl acrylate, 1,3-butanediol diacrylate, pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and pentaerythritol triacrylate; The second polymer monomer includes any one or more of 2,2,2-trifluoroethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate and 1,1,1,3,3,3-hexafluoroisopropyl methacrylate; The initiator includes any one or more of azobisisobutyronitrile, azobisisoheptylnitrile, benzoyl, dicumyl peroxide, dibenzoyl peroxide, potassium persulfate and ammonium persulfide.
3. The semi-solid battery electrolyte precursor according to claim 1 or 2, It is characterized in that The mass ratio of the first polymer monomer to the second polymer monomer is 3:1-1:1, preferably 3:1-2:1; Preferably, the mass of the initiator is 0.5-2 wt % of the total mass of the first polymer monomer and the second polymer monomer.
4. The semi-solid battery electrolyte precursor according to claim 1 or 2, It is characterized in that The semi-solid battery electrolyte precursor also includes a lithium salt and a solvent; The lithium salt includes any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate, lithium perchlorate, and lithium dioxalatoborate; The solvent includes any one or more of propylene carbonate, ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dimethyl ether and ethyl propionate.
5. The semi-solid battery electrolyte precursor according to claim 4, It is characterized in that The mass of the first polymer monomer is 0.5-5wt% of the total mass of the semi-solid battery electrolyte precursor, and the mass of the second polymer monomer is 0.5-2.5wt% of the total mass of the semi-solid battery electrolyte precursor; Preferably, the sum of the masses of the first polymer monomer and the second polymer monomer accounts for 1.5%-3% of the total mass of the semi-solid battery electrolyte precursor.
6. A semi-solid battery electrolyte, It is characterized in that The semi-solid battery electrolyte precursor is obtained by in-situ polymerization according to any one of claims 1 to 5.
7. A method for preparing a semi-solid battery, It is characterized in that include: The semi-solid battery electrolyte precursor according to any one of claims 1 to 5 is injected into a battery cell for in-situ polymerization.
8. The method for preparing a semi-solid-state battery according to claim 7, It is characterized in that The temperature of the in-situ polymerization is 50-70° C., and the time of the in-situ polymerization is 6-12 hours; Preferably, before the in-situ polymerization, the semi-solid battery electrolyte precursor is injected into the battery cell, vacuum-sealed, and left to stand for 24-50 hours.
9. The method for preparing a semi-solid-state battery according to claim 7, It is characterized in that include: The positive electrode sheet, the negative electrode sheet and the separator are prepared into a dry battery cell; Preferably, the positive electrode material of the positive electrode sheet includes any one or more of lithium cobalt oxide, ternary material, lithium iron phosphate, lithium-rich manganese-based material and spinel lithium manganese oxide; Preferably, the negative electrode material of the negative electrode sheet includes any one or more of graphite, amorphous carbon, lithium titanate, SiOx / C composite material and Sn-based composite material.
10. A semi-solid-state battery, It is characterized in that The semi-solid battery electrolyte according to claim 6 is prepared by the preparation method of the semi-solid battery according to any one of claims 7 to 9 or includes the semi-solid battery electrolyte according to claim 6.
Citation Information
Cited By
Gel polymer electrolyte precursor, gel polymer electrolyte, battery and preparation method of battery
CN122158698A
A gel polymer electrolyte precursor, a gel polymer electrolyte, and a battery and a method for manufacturing the same
CN122158698B
Semi-solid-state battery electrolyte precursor, semi-solid-state battery electrolyte, and semi-solid-state battery and preparation method therefor
WO2026056155A1
